Method for preserving high-activity iron particles based on synergistic polysaccharide polymer network structure

By encapsulating highly active iron particles in synergistic polysaccharide polymer network structure, the problem of oxidation reaction during preservation is solved, safety and activity are improved, and low-cost, environmentally friendly iron particles are preserved and applied.

CN119286003AActive Publication Date: 2025-01-10TONGJI UNIV
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202411448691.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-17
Publication Date
2025-01-10
Estimated Expiration
2044-10-17

AI Technical Summary

Technical Problem

The prior art has problems of poor safety, high cost and serious oxidation reaction when preserving highly active iron particles, resulting in a decrease in chemical activity and lack of effective methods to improve safety and maintain activity.

Method used

Using a method based on the synergistic polysaccharide polymer network structure, the polysaccharide polymer A and B aqueous solutions are prepared and mixed with highly active iron particles to form a dense three-dimensional network structure to isolate the contact between air and water molecules and prevent oxidation reactions.

Benefits of technology

It significantly improves the safety and chemical activity of highly active iron particles, forming a stable semi-solid composite system, suitable for large-scale preservation and application, and is cheap and environmentally friendly.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119286003A_ABST
    Figure CN119286003A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of environmental restoration, and discloses a method for preserving high-activity iron particles based on a synergistic polysaccharide polymer network structure. The method comprises the following steps: (1) preparing a polysaccharide polymer A aqueous solution and a polysaccharide polymer B aqueous solution; the concentration of the polysaccharide polymer A aqueous solution is 2-20g / L; (2) adding the polysaccharide polymer A aqueous solution into high-activity iron particles, and performing first stirring to obtain mixed slurry I; and (3) adding the mixed slurry I into the aqueous solution of the polysaccharide polymer B, carrying out secondary stirring to obtain mixed slurry II, standing, and after the polymer is fully crosslinked, forming a compact three-dimensional network structure to obtain the semi-solid composite system with the storage modulus being greater than or equal to 3Pa and the loss modulus being greater than or equal to 40Pa. The method provided by the invention not only improves the safety of the high-activity iron particles, but also effectively maintains the chemical activity of the high-activity iron particles.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of environmental restoration, and in particular to a method for preserving high-activity iron particles based on a synergistic polysaccharide polymer network structure. Background Art

[0002] Highly active iron particles have excellent physical and chemical properties, such as high specific surface area and strong reducibility, which make them widely used in environmental remediation, material science and catalysis. For example, highly active iron particles can effectively remove a variety of pollutants in the environment and can also be used as components of functional materials. However, due to their high surface activity, these particles are extremely sensitive to air. When exposed to air, they will quickly react with oxygen and release a large amount of heat, which can easily cause combustion. In addition, oxidation reactions with water molecules will also cause the activity of iron particles to decrease, affecting their original performance and effectiveness.

[0003] At present, the preservation of high-activity iron particles usually adopts simple physical methods, such as vacuum packaging, water solvent sealing, nitrogen protection, etc. However, these methods have problems such as poor safety, poor preservation effect, and high cost. For example, metal powders including zero-valent iron materials are currently mostly packaged in a vacuum form, such as publication number CN116198809A, publication number CN217624562U and publication number CN110641743A, which respectively disclose their own metal powder packaging devices, and publication number CN110271708A discloses a metal powder material packaging system and its use method.

[0004] The vacuum powder packaging method is not only costly, but also has the potential risk of severe oxidation and heat release when the package is damaged or unpacked. To enhance safety, low-cost water can be used as a solvent to prepare the iron particles into a slurry or suspension for storage. For example, publication number CN215324618U discloses a storage system for a zero-valent iron suspension, including a storage tank and a first stirring structure. However, during long-term storage and transportation, the continuous stirring of the suspension leads to a continuous oxidation reaction between the iron particles and water molecules (Fe 0 +2H2O→Fe 2+ +H2↑+2OH - ), the chemical activity of the iron particles is severely impaired.

[0005] In order to improve safety and reduce oxidation, common methods for stabilizing highly active iron particles mainly include the loading and surface modification of iron particles. The loading method mainly involves loading iron particles onto various carriers, such as biochar, zeolite or montmorillonite. For example, publication number CN202211362258.7 discloses a method for loading nano zero-valent iron using chitin microspheres as carriers, which improves the disadvantage of easy oxidation of iron particles and improves the activity of iron particles and the ability to be recycled repeatedly. However, the poor selectivity of the loading material may lead to compatibility issues between the carrier and the iron particles, and the cost and processing complexity of the loading material may also limit its practical application. The surface modification method is mainly to chemically modify the surface of the iron particles, such as sulfidation, amination, phosphating, etc. For example, publication number CN202311108797.2 discloses a method for calcining iron particles in a H-2S gas atmosphere to prepare sulfided zero-valent iron. The highly active iron particles after sulfidation are not easily oxidized, and can overcome problems such as oxidation and heat release during use. However, the surface modification method has problems such as weak adhesion of the modified layer, the modification process affecting the particle structure, and decreased reduction selectivity of the modified particles. Therefore, although the loading and surface modification methods have made some progress in stabilizing highly active iron particles, they still need to be further optimized and improved.

[0006] In summary, there is currently a lack of an effective method to improve the safety and maintain the chemical activity of highly active iron particles for large-scale preservation. Summary of the invention

[0007] The purpose of the present invention is: based on the above technical problems, the present invention provides a method for preserving high-activity iron particles based on a synergistic polysaccharide polymer network structure.

[0008] In order to achieve the above object, the first aspect of the present invention provides a method for preserving high-activity iron particles based on a synergistic polysaccharide polymer network structure, the method comprising the following steps:

[0009] (1) preparing a polysaccharide polymer A aqueous solution and a polysaccharide polymer B aqueous solution; the concentration of the polysaccharide polymer A aqueous solution is 2 to 20 g / L;

[0010] (2) adding the polysaccharide polymer A aqueous solution to the high-activity iron particles and performing a first stirring to obtain a mixed slurry I;

[0011] (3) adding the mixed slurry I to the aqueous solution of the polysaccharide polymer B, performing a second stirring to obtain a mixed slurry II, and allowing the mixed slurry to stand until the polymers are fully cross-linked to form a dense three-dimensional network structure, thereby obtaining a semi-solid composite system with a storage modulus ≥3Pa and a loss modulus ≥40Pa.

[0012] According to a particularly preferred embodiment, the preparation of the polysaccharide polymer A aqueous solution includes: adding the polysaccharide polymer A to deionized water, stirring evenly, heating in a water bath at 80°C for 60 minutes, and cooling to 45°C to obtain an aqueous solution of the polysaccharide polymer A; relative to 1g of the polysaccharide polymer A, the amount of the deionized water is 50 to 500mL.

[0013] According to a preferred specific embodiment, in step (1), preparing the polysaccharide polymer B aqueous solution includes: adding the polysaccharide polymer B to deionized water, stirring evenly, heating in a water bath at 80°C for 60 minutes, and cooling to 45°C to obtain the polysaccharide polymer B aqueous solution; relative to 1g of the polysaccharide polymer B, the amount of the deionized water used is 50 to 500mL.

[0014] Preferably, in step (1), the polysaccharide polymer A is konjac gum.

[0015] Further preferably, in step (1), the polysaccharide polymer B is selected from at least one of xanthan gum, guar gum, carrageenan, pectin and carrageenan.

[0016] Preferably, in step (2), the first stirring is performed in a homogenizer, and the conditions of the first stirring at least meet the following conditions: shear rate ≥ 10 4 s -1 .

[0017] Preferably, in step (3), the second stirring is performed in a homogenizer, and the conditions of the second stirring at least meet the following conditions: shear rate ≥ 10 4 s -1 .

[0018] Preferably, in step (3), the standing conditions at least meet the following conditions: normal temperature and normal pressure.

[0019] Further preferably, in step (3), in the semi-solid composite system, the mass ratio of iron particles to water molecules is 1:1-10, the mass ratio of iron particles to polysaccharide polymer A is 500-10:1, and the mass ratio of iron particles to polysaccharide polymer B is 1000-10:1.

[0020] Preferably, the concentration of the polysaccharide polymer A aqueous solution is the same as that of the polysaccharide polymer A aqueous solution, and the volume ratio of the polysaccharide polymer A aqueous solution to the polysaccharide polymer B aqueous solution is 1:0.5-1.

[0021] The method provided by the present invention has at least the following beneficial effects:

[0022] (1) The method provided by the present invention not only improves the safety of high-activity iron particles, but also effectively maintains their chemical activity; the method utilizes the synergistic effect of two natural polysaccharide polymers rich in hydroxyl groups, uses water as a solvent, and forms a dense three-dimensional network structure to encapsulate high-activity iron particles; polysaccharide polymers are abundant in nature, are environmentally friendly, and have low cost; a large number of active groups, mainly hydroxyl groups, are distributed on the polymer chains; certain polysaccharide polymers have synergistic effects and can cross-link with each other to form a denser three-dimensional network structure; the three-dimensional network structure formed by the synergistic effect of polymers to encapsulate high-activity iron particles can isolate the iron particles from contact with air, prevent rapid oxidation of the iron particles and large amounts of heat release, and significantly improve their safety; in addition, a large number of hydroxyl groups are distributed on these polymer chains, and the hydrogen bond interaction between the hydroxyl groups and the water molecules can achieve the binding of the water molecules, hindering the contact and reaction between the water molecules and the iron particles, thereby maintaining the chemical activity of the iron particles.

[0023] (2) The natural polysaccharide polymer used in the present invention is not only low-cost and easy to obtain, but also biodegradable and environmentally friendly. It can be used as a biological matrix in environmental remediation or wastewater treatment, bringing dual ecological benefits. In addition, the polysaccharide polymer has good water solubility. The semi-solid composite system formed in the later stage of the present invention can be stirred at high speed in water to release and disperse the iron particles, which is convenient for use after storage.

[0024] (3) The three-dimensional network structure constructed by the polysaccharide polymer in the present invention can effectively isolate the iron particles from contact with the air, prevent the iron particles from releasing a large amount of heat due to rapid oxidation, and greatly improve the safety during the storage process.

[0025] (4) The polysaccharide polymer in the present invention is rich in hydroxyl groups and can bind water molecules through hydrogen bonding interactions, thereby hindering the contact and reaction between water molecules and iron particles, thereby effectively maintaining the chemical activity of the iron particles.

[0026] (5) The composite system prepared by the present invention is a stable semi-solid state, which is convenient for storage and transportation in practical applications.

[0027] (6) The present invention does not require complicated equipment and operating procedures, is easy to promote on a large scale, and is suitable for a variety of scenarios where high-activity iron particles need to be preserved.

[0028] (7) The present invention has good versatility and is suitable for the storage of high-activity iron particles of different particle sizes and shapes. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 is a physical picture of the semi-solid composite system obtained in Example 1 of the present invention and a schematic diagram of its three-dimensional network structure;

[0030] Figure 2It is the XRD diffraction analysis diagram of iron particles after the products obtained in Example 1 of the present invention and Comparative Example 1 were stored for 60 days. DETAILED DESCRIPTION

[0031] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0032] As mentioned above, the first aspect of the present invention provides a method for preserving highly active iron particles based on a synergistic polysaccharide polymer network structure, the method comprising the following steps:

[0033] (1) preparing a polysaccharide polymer A aqueous solution and a polysaccharide polymer B aqueous solution; the concentration of the polysaccharide polymer A aqueous solution is 2 to 20 g / L;

[0034] (2) adding the polysaccharide polymer A aqueous solution to the high-activity iron particles and performing a first stirring to obtain a mixed slurry I;

[0035] (3) adding the mixed slurry I to the aqueous solution of the polysaccharide polymer B, performing a second stirring to obtain a mixed slurry II, and allowing the mixed slurry to stand until the polymers are fully cross-linked to form a dense three-dimensional network structure, thereby obtaining a semi-solid composite system with a storage modulus ≥3Pa and a loss modulus ≥40Pa.

[0036] In the present invention, the aqueous solution of polysaccharide polymer A and the aqueous solution of polysaccharide polymer B are important technical features, and there is a synergistic effect between the two. Specifically, the molecular chains of the two polymers contain rich functional groups and can form a dense three-dimensional network structure through various intermolecular interactions such as hydrogen bonds, hydrophobicity, and electrostatics.

[0037] In the present invention, the concentration of the polysaccharide polymer A aqueous solution is an important technical feature. If the concentration of the polysaccharide polymer A aqueous solution is too high, the viscosity of the aqueous solution is too large, and the iron particles are difficult to be evenly dispersed in the solution by stirring. If the concentration of the polysaccharide polymer A aqueous solution is too low, the viscosity of the aqueous solution is too low, and the iron particles are prone to gravity sedimentation in the solution. The inventors of the present invention have found that when the concentration of the polysaccharide polymer A aqueous solution is 2 to 20 g / L, the iron particles can be evenly dispersed in the solution by stirring and remain physically stable.

[0038] According to a particularly preferred embodiment, the preparation of the polysaccharide polymer A aqueous solution includes: adding the polysaccharide polymer A to deionized water, stirring evenly, heating in a water bath at 80°C for 60 minutes, and cooling to 45°C to obtain an aqueous solution of the polysaccharide polymer A; relative to 1g of the polysaccharide polymer A, the amount of the deionized water is 50 to 500mL.

[0039] According to a preferred specific embodiment, in step (1), preparing the polysaccharide polymer B aqueous solution includes: adding the polysaccharide polymer B to deionized water, stirring evenly, heating in a water bath at 80°C for 60 minutes, and cooling to 45°C to obtain the polysaccharide polymer B aqueous solution; relative to 1g of the polysaccharide polymer B, the amount of the deionized water used is 50 to 500mL.

[0040] In the present invention, water-soluble heating is required when preparing the polysaccharide polymer aqueous solution. The heating can promote the dissolution of the polymer, the expansion of the molecular chain, the interaction between molecules and the hydration, so as to ensure the formation of a dense three-dimensional network structure.

[0041] Preferably, in step (1), the polysaccharide polymer A is konjac gum.

[0042] Further preferably, in step (1), the polysaccharide polymer B is selected from at least one of xanthan gum, guar gum, carrageenan, pectin and carrageenan.

[0043] Preferably, in step (2), the first stirring is performed in a homogenizer, and the conditions of the first stirring at least meet the following conditions: shear rate ≥ 10 4 s -1 .

[0044] It should be noted that, in step (2), the stirring time of the first stirring is proportional to the total amount of the mixed slurry I, that is, the stirring time needs to be adjusted according to the total amount of the mixed slurry I.

[0045] According to a preferred specific implementation manner, in step (2), the stirring time of the first stirring is 30 to 120 seconds.

[0046] Preferably, in step (3), the second stirring is performed in a homogenizer, and the conditions of the second stirring at least meet the following conditions: shear rate ≥ 10 4 s -1 .

[0047] It should be noted that in step (3), the stirring time of the second stirring is proportional to the total amount of the mixed slurry II, that is, the stirring time needs to be adjusted according to the total amount of the mixed slurry I; the mixed slurry II is added with the polysaccharide polymer B aqueous solution on the basis of the mixed slurry I, so the stirring time is longer.

[0048] According to a preferred embodiment, in step (3), the stirring time of the second stirring is 45 to 240 seconds.

[0049] Preferably, in step (3), the standing conditions at least meet the following conditions: normal temperature and normal pressure.

[0050] It should be noted that in step (3), the mixed slurry II is allowed to stand for a period of time that is actually the cooling time of the mixed slurry II, that is, the period of time is determined by the mixed slurry II.

[0051] According to a preferred embodiment, in step (3), the standing time is 20 to 60 minutes.

[0052] Further preferably, in step (3), in the semi-solid composite system, the mass ratio of iron particles to water molecules is 1:1-10, the mass ratio of iron particles to polysaccharide polymer A is 500-10:1, and the mass ratio of iron particles to polysaccharide polymer B is 1000-10:1.

[0053] Preferably, the concentration of the polysaccharide polymer A aqueous solution is the same as that of the polysaccharide polymer A aqueous solution, and the volume ratio of the polysaccharide polymer A aqueous solution to the polysaccharide polymer B aqueous solution is 1:0.5-1.

[0054] In the present invention, the volume ratio of the aqueous solution of polysaccharide polymer A to the aqueous solution of polysaccharide polymer B is an important technical feature. If the volume ratio of the aqueous solution of polysaccharide polymer A to the aqueous solution of polysaccharide polymer B is too large or too small, the synergistic effect of the two is not significant enough. The inventors of the present invention have found that when the volume ratio of the aqueous solution of polysaccharide polymer A to the aqueous solution of polysaccharide polymer B is 1:0.5-1, the synergistic effect between the two is closer to the optimal state, and a dense three-dimensional network structure can be significantly formed.

[0055] The present invention will be described in detail below by way of examples. In the following examples, unless otherwise specified, the raw materials are all commercially available.

[0056] In the following examples, unless otherwise specified, the average particle size of the dried high-activity iron particles is 100 nm.

[0057] Example 1

[0058] This example is used to provide a method for preserving highly active iron particles based on a synergistic polysaccharide polymer network structure, the method comprising the following steps:

[0059] (1) 5 g of dry powder of konjac gum (referred to as polysaccharide polymer A) was added to 500 mL of deionized water, stirred evenly, and then heated in a water bath at 80° C. for 60 min to fully dissolve the mixture, and then cooled to 45° C. to obtain a 10 g / L konjac gum aqueous solution, which was referred to as polysaccharide polymer A aqueous solution. 5 g of dry powder of xanthan gum (referred to as polysaccharide polymer B) was added to 500 mL of deionized water, stirred evenly, and then heated in a water bath at 80° C. for 60 min to fully dissolve the mixture, and then cooled to 45° C. to obtain a 10 g / L xanthan gum aqueous solution, which was referred to as polysaccharide polymer B aqueous solution.

[0060] (2) Add 300 mL of the polysaccharide polymer A aqueous solution to 150 g of dried high-activity iron particles, transfer to a homogenizer, and heat for 10 min. 4 s -1 The mixture was stirred for 30 s at a shear rate of 1.5 to obtain a uniform mixed slurry I.

[0061] (3) Add the mixed slurry I to 200 mL of the polysaccharide polymer B aqueous solution, transfer to a homogenizer, and 4 s -1 The mixture was stirred at a shear rate of 50 s to obtain a mixed slurry II with an iron particle concentration of about 300 g / L. The mixture was allowed to stand at room temperature and pressure for 20 min until the polymer was fully cross-linked to form a dense three-dimensional network structure, and a semi-solid composite system with a storage modulus of 8 Pa and a loss modulus of 96 Pa was obtained (eg Figure 1 As shown); in the semi-solid composite system, the mass ratio of iron particles to water molecules is about 1:2.33, the mass ratio of iron particles to polysaccharide polymer A is 50:1, and the mass ratio of iron particles to polysaccharide polymer B is 75:1.

[0062] Example 2

[0063] The method of Example 1 is followed, except that in step (1), the amount of the dry powder of polysaccharide polymer A and the dry powder of polysaccharide polymer B are both 10 g, and the remaining steps and parameters are the same as in Example 1.

[0064] Among them, a polysaccharide polymer A aqueous solution with a concentration of 20 g / L and a polysaccharide polymer B aqueous solution with a concentration of 20 g / L were obtained.

[0065] Example 3

[0066] The method of Example 1 is followed, except that in step (1), the amount of the dry powder of the polysaccharide polymer A and the dry powder of the polysaccharide polymer B are both 1 g, and the remaining steps and parameters are the same as in Example 1.

[0067] Among them, a polysaccharide polymer A aqueous solution with a concentration of 2 g / L and a polysaccharide polymer B aqueous solution with a concentration of 2 g / L were obtained.

[0068] Example 4

[0069] The method of Example 1 was followed, except that in step (3), the amount of the polysaccharide polymer B aqueous solution was 300 mL, and the remaining steps and parameters were the same as in Example 1.

[0070] Comparative Example 1

[0071] Add 500 mL of deionized water to 150 g of dry high-activity iron particles and 4 s -1 The mixture was stirred for 50 s at a shear rate of 1.5 to obtain a high-activity iron particle aqueous solution with an iron particle concentration of 300 g / L.

[0072] In this comparative example, no polymer was added and no network structure was formed.

[0073] Comparative Example 2

[0074] The method of Example 1 was followed, except that in step (1), after the polysaccharide polymer A and the polysaccharide polymer B were dissolved in deionized water, they were not placed in a water bath at 80° C. for heating. The remaining steps and parameters were the same as those of Example 1.

[0075] In this comparative example, since water bath heating is not performed, it is difficult or impossible to form a dense three-dimensional network structure.

[0076] Comparative Example 3

[0077] The method of Example 1 was followed, except that in step (3), the aqueous solution of polysaccharide polymer B was not added to the mixed slurry I. The remaining steps and parameters were the same as in Example 1.

[0078] In this comparative example, only the aqueous solution of polysaccharide polymer A was added, and no aqueous solution of polysaccharide polymer B was added, which lacks the synergistic effect between different polymers.

[0079] The products obtained in the above examples and comparative examples were stored at room temperature, pressure and sealed for 60 days, and then XRD diffraction analysis and Fe(0) content determination were performed respectively. For example, the comparison results of Fe(0) content of iron particles obtained in Examples 1 to 3 of the present invention and Comparative Example 1 after 60 days of storage are shown in Table 1.

[0080] Table 1

[0081] Example No. Example 1 Example 2 Example 3 Comparative Example 1 Fe(0) content 51.1%±2.2% 53.3%±3.1% 25.4%±1.1% 16.2%±1.8%

[0082] As can be seen from Table 1, the Fe(0) content of the iron particles of the products obtained in Examples 1 to 3 of the present invention after storage for 60 days is higher than the Fe(0) content of the iron particles of the product obtained in Comparative Example 1 after storage for 60 days, indicating that the polymer network effectively preserves the iron particles.

[0083] For example, Figure 2 The figure is the XRD diffraction analysis result of iron particles after the products obtained in Example 1 and Comparative Example 1 were stored for 60 days.

[0084] Depend on Figure 2 It can be seen that the XRD results of the product obtained in Example 1 after storage for 60 days show that the main component of the iron particles is Fe(0), indicating that the iron particles have a good preservation effect. The XRD results of the product obtained in Comparative Example 1 after storage for 60 days show that the iron particles contain a large amount of iron oxide components (Fe2O3, FeOOH, and Fe3O4), indicating that the iron particles have undergone significant oxidation loss and poor preservation effect.

[0085] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A method for preserving highly active iron particles based on a synergistic polysaccharide polymer network structure, characterized in that: The method comprises the following steps: (1) preparing a polysaccharide polymer A aqueous solution and a polysaccharide polymer B aqueous solution; the concentration of the polysaccharide polymer A aqueous solution is 2 to 20 g / L; (2) adding the polysaccharide polymer A aqueous solution to the high-activity iron particles and performing a first stirring to obtain a mixed slurry I; (3) adding the mixed slurry I to the aqueous solution of the polysaccharide polymer B, performing a second stirring to obtain a mixed slurry II, and allowing the mixed slurry to stand until the polymers are fully cross-linked to form a dense three-dimensional network structure, thereby obtaining a semi-solid composite system with a storage modulus ≥3Pa and a loss modulus ≥40Pa.

2. The method according to claim 1, wherein: In step (1), preparing the polysaccharide polymer A aqueous solution comprises: adding the polysaccharide polymer A to deionized water, stirring evenly, heating in a water bath at 80° C. for 60 minutes, and cooling to 45° C. to obtain the polysaccharide polymer A aqueous solution; the amount of the deionized water used is 50 to 500 mL relative to 1 g of the polysaccharide polymer A; And / or, in step (1), preparing the polysaccharide polymer B aqueous solution includes: adding the polysaccharide polymer B to deionized water, stirring evenly, heating in a water bath at 80°C for 60 minutes, and cooling to 45°C to obtain the polysaccharide polymer B aqueous solution; relative to 1g of the polysaccharide polymer B, the amount of the deionized water is 50 to 500mL.

3. The method according to claim 1 or 2, wherein: In step (1), the polysaccharide polymer A is konjac gum; And / or, in step (1), the polysaccharide polymer B is selected from at least one of xanthan gum, guar gum, carrageenan, pectin and carrageenan.

4. The method according to claim 1 or 2, wherein: In step (2), the first stirring is performed in a homogenizer, and the conditions of the first stirring at least meet the following conditions: shear rate ≥ 10 4 s -1 .

5. The method according to claim 1 or 2, wherein: In step (3), the second stirring is performed in a homogenizer, and the conditions of the second stirring at least meet the following conditions: shear rate ≥ 10 4 s -1 .

6. The method according to claim 1 or 2, wherein: In step (3), the static conditions at least meet the following conditions: normal temperature and normal pressure.

7. The method according to claim 1 or 2, wherein: In step (3), in the semi-solid composite system, the mass ratio of iron particles to water molecules is 1:1-10, the mass ratio of iron particles to polysaccharide polymer A is 500-10:1, and the mass ratio of iron particles to polysaccharide polymer B is 1000-10:

1.

8. The method according to claim 1 or 2, wherein: The concentration of the polysaccharide polymer A aqueous solution is the same as that of the polysaccharide polymer A aqueous solution, and the volume ratio of the polysaccharide polymer A aqueous solution to the polysaccharide polymer B aqueous solution is 1:0.5-1.

Citation Information

Patent Citations

  • Metal powder material packaging device and using method

    CN110271708A

  • Metal powder packaging device

    CN110641743A

  • Chitin microsphere loaded nano zero-valent iron material as well as preparation method and application thereof

    CN115739034A

  • Metal powder packaging machine

    CN116198809A

  • A sulfurized nano-zero-valent iron material, its preparation method and application

    CN117023757B